Natural carbon fixation and advances in synthetic engineering for redesigning and creating new fixation pathways - Sulamita Santos Correa; Junia Schultz; Kyle J. Lauersen; Alexandre Soares Rosado (Journal of Advanced Research, 2023)
Background: Autotrophic carbon fixation is the primary route through which organic carbon enters the biosphere, and it is a key step in the biogeochemical carbon cycle. The Calvin–Benson–Bassham pathway, which is predominantly found in plants, algae, and some bacteria (mainly cyanobacteria), was previously considered to be the sole carbon-fixation pathway. However, the discovery of a new carbon-fixation pathway in sulfurous green bacteria almost two decades ago encouraged further research on previously overlooked ancient carbon-fixation pathways in taxonomically and phylogenetically distinct microorganisms. Aim of Review: In this review, we summarize the six known natural carbon-fixation pathways and outline the newly proposed additions to this list. We also discuss the recent achievements in synthetic carbon fixation and the importance of the metabolism of thermophilic microorganisms in this field. Key Scientific Concepts of Review: Currently, at least six carbon-fixation routes have been confirmed in Bacteria and Archaea. Other possible candidate routes have also been suggested on the basis of emerging “omics” data analyses, expanding our knowledge and stimulating discussions on the importance of these pathways in the way organisms acquire carbon. Notably, the currently known natural fixation routes cannot balance the excessive anthropogenic carbon emissions in a highly unbalanced global carbon cycle. Therefore, significant efforts have also been made to improve the existing carbon-fixation pathways and/or design new efficient in vitro and in vivo synthetic pathways.